Leachate treatment using sequential microwave and algal photo-bioreactor: Effect of pretreatment on reactor performance and biomass productivity. (1st June 2022) - Tripathy, Binay Kumar; Kumar, Mathava
Abstract: The present study aims to design a lab-scale hybrid reactor, primarily focused on the removal of organics, nutrients, heavy metal and other toxic compounds, thereby, minimizing risk associated with the disposal of landfill leachate. The potential of a designed hybrid treatment system (i.e., sequential microwave (MW) with algal bioreactor) with and without pretreatment, i.e., coagulation-flocculation (CF), was evaluated based on several parameters. The CF pretreatment under optimized conditions has resulted in 90% turbidity and 76% COD removals from leachate; furthermore, the MW treatment achieved 91% ammonia removal from raw leachate. As a result, substantial algal growth was observed in the preliminary algal batch experiment conducted with MW and MW-CF treated samples. Subsequently, leachate treatment was carried out using sequencing batch reactor (SBR) systems, i.e., MW-algal SBR and CF-MW-algal SBR. Algal biomass growth and increment in DO level were observed in algal-SBR experiments. Under the optimized reactor conditions, TN and TP removal rates in the algal-SBR were found to be 1.67–20 mg/L/d and 0.6–9.6 mg/L/d, respectively. The majority of heavy metals present in the leachate were removed due to algal-uptake (mainly Zn 2+ ) and bio-sorption (total-Fe, Cu 2+ and Pb 2+ ). Meanwhile, some amount of energy can be recovered from algal biomass as inferred from the cost benefit analysis. Overall, the hybrid treatment combining MW and algal-SBR has shown immense potential for sustainable leachate treatment. Graphical abstract: Image 1 Highlights: Removal of ammonia due to microwave enhanced algal growth in algal photo-bioreactor. Coagulation process enhanced the light penetration in algal photo-bioreactor. DO increased after 3 d acclimatization period in the algal SBR system. TN removal rate in the algal SBR system varied between 1.67 and 20 mg/L/d. Efficient Zn 2+ and total-Fe removal were observed during the algal SBR treatment.